LGBTIQ+ Students in Higher Education Institutions: Findings and Trends - Nava Cruz, Raúl (2024)
This article aims to identify key trends in the experiences of LGBTQIA+ students navigating higher education institutions in Latin America. Employing a qualitative documentary methodology and a systematic review of information, a search was conducted in databases such as Google Scholar, Scielo, Redalyc, and Scopus, focusing on scientific journal publications from 2014 to 2024. A total of 26 articles were selected and analyzed using a matrix. The research reveals a complex reality for LGBTQIA+ students. While universities often present themselves as inclusive spaces, these students continue to face both overt and subtle forms of violence and discrimination. They also perceive a lack of effective institutional mechanisms to prevent and address such discrimination. Conversely, universities are viewed as more inclusive and accepting environments compared to other aspects of students' lives and prior educational experiences. Despite developing resilient strategies, structural barriers persist. These include limited diversity in curricula and administrative procedures that do not adequately consider sexual diversity. This highlights the urgent need for more effective policies and actions to ensure the inclusion of LGBTQIA+ students